Comparison of multimode GRIN-fiber Raman lasers with FBG and random DFB cavity. Issue 1 (1st April 2022) - Chen, Yizhu; Fan, Chenchen; Yao, Tianfu; Xiao, Hu; Xu, Jiangming; Leng, Jinyong; Zhou, Pu; Kuznetsov, Alexey G.; Nemov, Ilya N.; Wolf, Alexey A.; Kablukov, Sergey I.; Podivilov, Evgeny V.; et al.
Abstract: Raman lasing in multimode GRIN fibers is accompanied by sufficient improvement of the output beam quality in comparison with that for pump radiation, which offers opportunities to wavelength-agile fiber lasers of new type. Here we compare power scaling and brightness enhancement capabilities of Raman laser based on multimode GRIN-fiber of 62.5/125 um core/cladding diameters pumped by ∼700 W multimode source with beam quality M 2 ∼10, performed in two different cavity configurations: 1) linear cavity based on two fiber Bragg gratings and 2) half-open cavity with one FBG and random distributed feedback via Rayleigh backscattering along the GRIN fiber.